1
$\begingroup$

I am kind of stuck on the following...

There is a cubic equation like this: $x^3-px^2+qx-r=0$

We are given that the three roots are: $ak^{-1},a,ak$ for some constants $k$ and $a$. Also given (actually one has to deduce this) that $q/p=a$ is one root, and that the product of the other two is $(q/p)^2$ one has to deduce that the roots are in geometric progression... (also note that $r=a^3=(q/p)^3$)

If we let the three roots be: $\alpha,\beta,\gamma$ then $\gamma=\alpha r^2$ and $\beta=\alpha r$. We know that $\alpha \gamma = (q/p)^2$ and that $\alpha \alpha r^2=\alpha^2 r^2=(q/p)^2$. And now I have no clue what to do.

$\endgroup$
0
$\begingroup$

Use that

$$x^3-px^2+qx-r=\left(x-\frac{a}{k}\right)(x-a)(x-ak)=x^3-\left(ak+a+\frac{ a}{k}\right)x^2+\left(a^2k+a^2+\frac{a^2}{k}\right)x-a^3.$$ Then, $\displaystyle\frac{q}{p}=a.$ Moreover, the product of the other two roots is $$ak\cdot \frac{a}{k}=a^2=\left(\frac{q}{p}\right)^2.$$ Finally,

$$ak\cdot a\cdot \frac{a}{k}=a^3=r=\left(\frac{q}{p}\right)^3.$$

$\endgroup$
  • $\begingroup$ brain freeze.... So we do not show explicitly that one root is $\alpha$, then the other one is $\alpha r$ and the third $\alpha r^2$... rather we use the product of the three roots.. so I had the answer all this time, not realizing it $\endgroup$ – i squared - Keep it Real Jan 16 '16 at 18:25

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.